Magical Realism in Matt Haig’s The Midnight Library - Pramesti, Arninta Beatris; Rahayu, Anik Cahyaning (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research discusses about Magical Realism in Matt Haig’s The Midnight Library. The novel, as the data source, tells about of the main character, Nora seed, a woman who finds herself in a mysterious library between life and death after her suicide attempt. Each book in the library contains a different version of Nora’s life based on the choices she could have made. This library represents a different version of her life, each based on choices she could have made differently. The scope focuses on the elements of magical realism and the roles of the midnight library as a liminal space. This research focuses on revealing the elements of magical realism and roles of the midnight library as a liminal space. This research uses theory of the elements of magical realism by Wendy B. Faris, which consists of the irreducible element, the phenomenal world, unsetting doubts, merging realm, and disruption of time, space and identity. This research uses descriptive qualitative method and uses intrinsic approach. The novel incorporates the library as a liminal space that bridges in life and death, between reality and imagination, as well as temporal and spatial boundaries. The result of the analysis indicates that the novel can be categorized as the literary work of magical realism because the elements of magical realism can be found in the novel and the library in this novel represents as a place between life and death, temporal and spatial, and the transitionary of the library.